The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1287/trsc.1120.0445
|View full text |Cite
|
Sign up to set email alerts
|

Branch and Price for the Time-Dependent Vehicle Routing Problem with Time Windows

Abstract: This paper presents a branch-and-price algorithm for the time-dependent vehicle routing problem with time windows (TDVRPTW). We capture road congestion by considering time-dependent travel times, i.e., depending on the departure time to a customer, a different travel time is incurred. We consider the variant of the TDVRPTW where the objective is to minimize total route duration and denote this variant the duration minimizing TDVRPTW (DM-TDVRPTW). Because of time dependency, vehicles' dispatch times at the depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 43 publications
0
97
0
3
Order By: Relevance
“…An exact algorithm for the TDVRPTW was presented by Dabia, Ropke, Van Woensel, and De Kok (2013) using a modified set of the well-known instances of Solomon (1987) for the VRPTW. Speed patterns in links between nodes were allocated randomly and the solution approach was based on a pricing algorithm utilising a column generation and a labelling algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An exact algorithm for the TDVRPTW was presented by Dabia, Ropke, Van Woensel, and De Kok (2013) using a modified set of the well-known instances of Solomon (1987) for the VRPTW. Speed patterns in links between nodes were allocated randomly and the solution approach was based on a pricing algorithm utilising a column generation and a labelling algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Except software package service as programming solver, MP-based approaches observed in the field of three targeted fields are as follows: Branch-and-Bound [34], Branch-and-Cut [146], Branch-and-Price [219], Branch-and-Cut-and-Price [142], Dynamic Programming [220], Lagrangian Relaxation [221], Column Generation [222], Set Partitioning [223], Constraint Programming [224], Goal Programming [225], Set Covering [226], and so forth. As shown in Table 1, it can be observed that the most frequently used mathematical programming-based method in the field of scheduling is B&B (Branch-and-Bound), while B&P (Branch-and-Price) is the most popular branching method in the field of VRP.…”
Section: Mathematical Programming-based Approachesmentioning
confidence: 99%
“…It was formulated as an integer programming model to minimize makespan of the whole discharging course and solved by a two stages tabu search algorithm. Dabia et al [4] presented a branch and price algorithm for time-dependent vehicle routing problem with time windows. Han et al [5] considered a vehicle routing problem with uncertain travel times in which a penalty is incurred for each vehicle that exceeds a given time limit and given robust scenario approach for the vehicle routing problem.…”
Section: Literature Reviewmentioning
confidence: 99%